Cytokine Profiles Associated With Acute COVID-19 and Long COVID-19 Syndrome - Queiroz, Maria Alice Freitas; Neves, Pablo Fabiano Moura das; Lima, Sandra Souza; Lopes, Jeferson da Costa; Torres, Maria Karoliny da Silva; Vallinoto, Izaura Maria Vieira Cayres; Bichara, Carlos David Araújo; Santos, Erika Ferreira dos; de Brito, Mioni Thieli Figueiredo Magalhães; da Silva, Andréa Luciana Soares; Leite, Mauro de Meira; da Costa, Flávia Póvoa; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The duration and severity of COVID-19 are related to age, comorbidities, and cytokine synthesis. This study evaluated the impact of these factors on patients with clinical presentations of COVID-19 in a Brazilian cohort. A total of 317 patients diagnosed with COVID-19 were included; cases were distributed according to clinical status as severe (n=91), moderate (n=56) and mild (n=170). Of these patients, 92 had acute COVID-19 at sample collection, 90 had already recovered from COVID-19 without sequelae, and 135 had sequelae (long COVID syndrome). In the acute COVID-19 group, patients with the severe form had higher IL-6 levels (p=0.0260). In the post-COVID-19 group, there was no significant difference in cytokine levels between groups with different clinical conditions. In the acute COVID-19 group, younger patients had higher levels of TNF-α, and patients without comorbidities had higher levels of TNF-α, IL-4 and IL-2 (p<0.05). In contrast, patients over age 60 with comorbidities had higher levels of IL-6. In the post-COVID-19 group, subjects with long COVID-19 had higher levels of IL-17 and IL-2 (p<0.05), and subjects without sequelae had higher levels of IL-10, IL-6 and IL- 4 (p<0.05). Our results suggest that advanced age, comorbidities and elevated serum IL-6 levels are associated with severe COVID-19 and are good markers to differentiate severe from mild cases. Furthermore, high serum levels of IL-17 and IL-2 and low levels of IL-4 and IL-10 appear to constitute a cytokine profile of long COVID-19, and these markers are potential targets for COVID-19 treatment and prevention strategies.